Effect of synbiotic supplementation on obesity and gut microbiota in obese adults: a double-blind randomized controlled trial - Niu, Xiaokang; Zhang, Qi; Liu, Julong; Zhao, Yuyang; Shang, Nan; Li, Shusen; Liu, Yinghua; Xiong, Wei; Sun, Erna; Zhang, Yong; Zhao, Hongfeng; Li, Yixuan; et al. (Frontiers in Nutrition, 2024)
Background: Synbiotics, combining specific probiotics and selected prebiotics, may benefit health issues like obesity, but evidence remains inconsistent. Objective: This study aimed to verify the effect of a pre-screened synbiotics combination (containing Bifidobacterium animalis subsp. lactis MN-Gup (MN-Gup), galacto-oligosaccharides (GOS) and xylo-oligosaccharides (XOS)) on obesity in the population. Methods: In a randomized, double-blind, placebocontrolled trial, 80 individuals with obesity consumed daily synbiotics (containing MN-Gup 1 × 10 11 CFU/day, GOS 0.7g/day, and XOS 0.7g/day) or placebo for 12 weeks. Body composition, blood lipids, serum hormone, bile acids, and gut microbiota were measured preand post-intervention. Results: Synbiotics supplementation significantly decreased body fat percentage, waist, and serum low-density lipoprotein cholesterol (LDL-C), increased peptide YY, cholecystokinin, oxyntomodulin, GSH (glutathione peroxidase) in individuals with obesity. Additionally, synbiotic supplementation led to an enrichment of beneficial bacteria and bile acids (Chenodeoxycholic Acid (CDCA). Bifidobacterium and Romboutsia were significantly positively correlated with CDCA. A more favorable effect was observed in individuals with obesity and abnormal LDL-C compared to those without dyslipidemia. Conclusion: 12-week synbiotics intervention reduced body fat percentage, waist, and serum LDL-C, especially in individuals with obesity and abnormal LDL-C. The possible mechanisms may be related to changes in gut microbiota, bile acids and gut hormones. The study was registered at Chictr.org.cn with a registration number of ChiCTR2200064156.